Subsidiary autonomy and performance in Japanese multinationals in Europe - Kawai, Norifumi; Strange, Roger (International business review, 2014)
•Subsidiary perceptions of autonomy were not found to have a direct and positive impact on the performance of foreign subsidiaries.•We show that subsidiary autonomy is more favourable when technology is changing rapidly and unpredictably.•Our research suggests that the effectiveness of subsidiary autonomy in promoting the performance of overseas subsidiaries is enhanced under high levels of expatriate involvement. Notwithstanding the growing body of research on headquarters–subsidiary relationships, the conditions under which subsidiary autonomy leads to enhanced subsidiary performance is still a subject of debate. This study adopts a contingency approach and investigates the effects of external uncertainties and intra-MNE coordination on the performance benefits of subsidiary autonomy. The empirical analysis is based upon cross-sectional data collected from 88 European subsidiaries of Japanese MNEs. Our findings show that subsidiary autonomy has a greater impact upon performance (a) under conditions of technological uncertainty; and (b) when expatriate involvement is high, as the subsidiary can reap the full benefits of entrepreneurial capabilities and enjoy resource interdependencies through interactions with the parent simultaneously. MNC executives should aim for an appropriate balance between subsidiary autonomy and these internal and external factors so that the subsidiaries achieve superior performance.